A mucosite oral grave em pacientes pediátricos oncológicos: um estudo com análise de sobrevivência - Damascena, Lecidamia Cristina Leite (2017)
Severe oral mucositis is an adverse event commonly presented by children undergoing oncologic treatment. The objective of this study was to investigate the occurrence of severe oral mucositis and the associated factors in pediatric patients with hematological tumors and solid tumors submitted to oncological treatment, attended at a reference hospital in the city of João Pessoa / PB by means of survival analysis. This was a longitudinal, descriptive, observational, inductive study in order to explain the time of onset of severe oral mucositis in pediatric patients submitted to cancer treatment. The study was carried out at the Hospital Napoleão Laureano, located in the city of João Pessoa / PB, in the pediatric ward, from 2013 to 2017, with a target population of 0-19 years old pediatric patients submitted to an oncological treatment regimen, attended in the pediatrics sector of said hospital, with a sample of 142 participants. The data were collected from a form with information regarding the sociodemographic aspects related to the patient's health condition and the modified OAG (Oral Assessment Guide). A descriptive and inferential analysis was performed using the Kaplan-Meier method and the semi-parametric Cox model. The results show that the median time to onset of severe oral mucositis in patients with haematological and solid tumors was 35.3 and 77.1 days, respectively. The Cox model revealed that changes in the number of leukocytes, platelets and chemotherapy of the natural product class are risk factors for the appearance of oral mucositis in patients with haematological tumors and, for patients with solid tumors, non-pardos, presence of metastasis, changes in creatinine levels, combination of surgery, chemotherapy and radiotherapy, and the administration of chemotherapeutic agents of the miscellaneous group were related to the occurrence of this condition. It is concluded that the time of onset of severe oral mucositis varied for both groups and those for patients with hematologic tumors, blood changes and chemotherapy were considered risk factors for its occurrence; for patients with solid tumors, the individual's own characteristics related to treatment and disease appeared as a risk condition for the occurrence of severe oral mucositis.